2006
DOI: 10.1136/tc.2005.012187
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid reimbursement for prenatal smoking intervention influences quitting and cessation

Abstract: Background: 40% of births in the USA are covered by Medicaid and smoking is prevalent among recipients. The objective of this study was to evaluate the association between levels of Medicaid coverage for prenatal smoking cessation interventions on quitting during pregnancy and maintaining cessation after delivery. Methods: Population based survey study of 7513 post-partum women from 15 states who: participated in Pregnancy Risk Assessment Monitoring System (PRAMS) during 1998-2000; smoked at the beginning of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 25 publications
1
26
0
1
Order By: Relevance
“…Studies (41-45) have consistently found that higher cigarette taxes reduce the prevalence of prenatal smoking and the number of LBW, PTB and SIDS cases, and two studies (42, 43) found the highest price sensitivity for younger pregnant women. Medicaid policies supporting pharmacotherapy and behavioral therapy (46, 47) and more generally behavioral interventions (48, 49) have been found effective in reducing prenatal smoking. Other potentially effective policies are raising the minimum legal purchase age for tobacco to 21 (50), and media campaigns and graphic health warnings directed at discouraging maternal smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Studies (41-45) have consistently found that higher cigarette taxes reduce the prevalence of prenatal smoking and the number of LBW, PTB and SIDS cases, and two studies (42, 43) found the highest price sensitivity for younger pregnant women. Medicaid policies supporting pharmacotherapy and behavioral therapy (46, 47) and more generally behavioral interventions (48, 49) have been found effective in reducing prenatal smoking. Other potentially effective policies are raising the minimum legal purchase age for tobacco to 21 (50), and media campaigns and graphic health warnings directed at discouraging maternal smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies have focused solely on women before, during, or after pregnancy. An earlier study (Petersen, Garrett, Melvin, & Hartmann, 2006) linked 1998 coverage cessation data to 1998-2000 PRAMS data and found that quit rates were significantly higher in states with Medicaid coverage of pharmacotherapies or counseling than in states without cessation service coverage. However, this analysis was limited to only one year of coverage data, and only a few states changed policies during their short study period.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, systematic reviews of pay-for-performance schemes that are targeted at doctors suggest that financial rewards can improve the quality of care. 2,25 On the basis of these studies, it would seem reasonable to conclude that the QOF is likely to have effected changes in utilisation that would make payments cost-effective. However, the QOF may also have had unintended consequences, such as encouraging inappropriate 'exception reporting' of patients to improve apparent performance.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%